BUSINESS AVIATION MANAGEMENT AND MARKET (Perner's Contacts, 2016)
The main aim of this article is to analyse one sector of air transportation, Business Aviation. The paper describes Business Aviation Management in middle size company. European market is shown in graphs related to operation in this market and introduces possibilities of new potential business aviation markets. As the business aviation is unknown part of air transport the articles reveals some interested facts about it and focuses also on its natural safety.
Keywords: Business Aviation; Business Aviation Safety; Europe market